A clinical pathway for the management of Peyronie's disease: integrating clinical guidelines from the International Society of Sexual Medicine, American Urological Association and European Urological Association. (16th June 2020) - Chung, Eric; Gillman, Michael; Tuckey, John; La Bianca, Shane; Love, Chris
Abstract : Objective: To provide a clinical framework and key guideline statements to assist clinicians in the evidence‐based management of Peyronie's disease (PD). Methods: We conducted a review of the published literature relevant to PD management, with an emphasis on published clinical guidelines. References used in the text have been assessed according to their level of evidence, and guideline recommendations have been graded based on the Oxford Centre for Evidence‐based Medicine Levels of Evidence. Results: The management of PD involves taking a detailed penile and sexual history, with a focused penile examination to identify plaque and hourglass deformity, and digital photographs of the erect curved (deformed) penis. Penile colour Duplex ultrasonography evaluates tunical plaque and underlying cavernosal smooth muscle and blood flow variables. The current therapy for PD can be divided into two main groups, namely, medical therapy and penile reconstructive surgery, and the patient should be counselled on the benefits and risks of each treatment option. Conclusions: Peyronie's disease remains a clinical challenge and presents a considerable therapeutic dilemma as the current therapy addresses existing penile curvature only and is not very effective in preventing future penile fibrosis and/or reversing underlying erectile dysfunction.